2005
DOI: 10.1007/s11172-005-0376-3
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion complexes of spin-labeled indoles with cyclodextrins in aqueous solutions

Abstract: Guest host complexes of β and γ cyclodextrins (CDs) with two spin labeled indole de rivatives having the same molecular weights but different structures were studied by EPR spectroscopy in aqueous solutions and semiempirical quantum chemical calculations of these systems were carried out. In the presence of CD the polarity of the NO group environment decreases and the rotational correlation time (τ) of guest molecules increases. Both indole derivatives form 1 : 1 complexes with γ CD, the binding constants of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…On the basis of ESR spectral simulation, it was possible to determine the orientation of the indole ring in relation to the plane of the host molecule and the rotational diffusion coefficients of the complexes, which corresponded to the hydrodynamic volume of one gamma-CD molecule. In contrast to the complexes with gamma-CD the rotational correlation times, T, of the complexes with beta-CD correspond to a hydrodynamic volume which much exceeds the volume of a single beta-CD molecule 157 . The synthesis is reported of two isomers of permethylated beta-cyclodextrin, labelled with paramagnetic TEMPO moieties attached on the same rim of the cavity, whose host-guest properties were subsequently investigated by EPR spectroscopy 158 .…”
Section: Studies On Enzymesmentioning
confidence: 94%
“…On the basis of ESR spectral simulation, it was possible to determine the orientation of the indole ring in relation to the plane of the host molecule and the rotational diffusion coefficients of the complexes, which corresponded to the hydrodynamic volume of one gamma-CD molecule. In contrast to the complexes with gamma-CD the rotational correlation times, T, of the complexes with beta-CD correspond to a hydrodynamic volume which much exceeds the volume of a single beta-CD molecule 157 . The synthesis is reported of two isomers of permethylated beta-cyclodextrin, labelled with paramagnetic TEMPO moieties attached on the same rim of the cavity, whose host-guest properties were subsequently investigated by EPR spectroscopy 158 .…”
Section: Studies On Enzymesmentioning
confidence: 94%
“…From these figures, it can be observed that, generally, there is a satisfactory agreement between the experimental and simulated ESR spectra. However, as was emphasized earlier, 24,25,34 the parameters of the molecular rotation of the spin probes, rotational frequencies, and angular amplitudes cannot be determined unambiguously using the A zz ′ (or S) values, since the same A zz ′ or S values can be obtained by varying the slow rotation frequency in the full solid angle (4π) or by varying the angular amplitude in the fast librations model. In particular, it is difficult to correctly and unambiguously choose between these two limiting models of molecular motion for the often-occurring case of high S values (S ≥ 0.9) from the simulations of the conventional first-harmonic ESR spectra because of the large inhomogeneous broadening.…”
Section: T H I S C O N T E N T Imentioning
confidence: 97%
“…Sample capillaries were positioned along the symmetry axis of the standard 4 mm quartz ESR sample tube that contained mineral oil for thermal stability. The root-meansquare microwave magnetic field ⟨B 1 2 ⟩ 1/2 measurement for a "point" sample of aqueous peroxylamine disulfonate with known T 1 and T 2 24 values gave a maximum value of 0.51 G. The low-power ESR spectra were recorded at a power of 26 dB (H 1 ≅ 0.0255 G) and a small modulation amplitude, which rules out spectral distortion. The STESR spectra, i.e., the ESR absorption spectra detected on the second harmonics of modulation in the 90°phase with a modulation field (V 2 ′), were recorded under partial microwave saturation, essentially as described in ref 27.…”
Section: Experimental and Computationalmentioning
confidence: 99%
“…In contrast to the complexes with gamma-CD the rotational correlation times, T, of the complexes with beta-CD correspond to a hydrodynamic volume which much exceeds the volume of a single beta-CD molecule. 39 The synthesis is reported of two isomers of permethylated beta-cyclodextrin, labelled with paramagnetic TEM-PO moieties attached on the same rim of the cavity, whose host-guest properties were subsequently investigated by ESR spectroscopy. 40 It is known that the ESR spectra of cyclodextrins (CD) labelled with TEMPO are sensitive to the incorporation of large guest molecules.…”
Section: Biological Systemsmentioning
confidence: 99%